ADVANTAGES OF RAPID METHOD FOR DETERMINING SCALE MASS AND DECARBURIZED LAYER OF ROLLED COIL STEEL - Parusov, E. V.; Sychkov, A. B.; Gubenko, S. I.; Chuiko, I. N.; Sahura, L. V. (Science and Transport Progress, 2016)
Purpose. To determine the universal empirical relationships that allow for operational calculation of scale mass and decarbonized layer depth based on the parameters of the technological process for rolled coil steel production. Methodology. The research is carried out on the industrial batches of the rolled steel of SAE 1006 and SAE 1065 grades. Scale removability was determined in accordance with the procedure of «Bekaert» company by the specifi-cations: GA-03-16, GA-03-18, GS-03-02, GS-06-01. The depth of decarbonized layer was identified in accordance with GOST 1763-68 (M method). Findings. Analysis of experimental data allowed us to determine the rational temperature of coil formation of the investigated steel grades, which provide the best possible removal of scale from the metal surface, a minimal amount of scale, as well as compliance of the metal surface color with the require-ments of European consumers. Originality. The work allowed establishing correlation of the basic quality indicators of the rolled coil high carbon steel (scale mass, depth of decarbonized layer and inter-laminar distance in pearlite) with one of the main parameters (coil formation temperature) of the deformation and heat treatment mode. The re-sulting regression equations, without metallographic analysis, can be used to determine, with a minimum error, the quantitative values of the total scale mass, depth of decarbonized layer and the average inter-lamellar distance in pearlite of the rolled coil high carbon steel. Practical value. Based on the specifications of «Bekaert» company (GA-03-16, GA-03-18, GS-03-02 and GS-06-01) the method of testing descaling by mechanical means from the surface of the rolled coil steel of low- and high-carbon steel grades was developed and approved in the environment of PJSC «ArcelorMittal Kryvyi Rih». The work resulted in development of the rapid method for determination of total and remaining scale mass on the rolled coil steel surface of low- and high-carbon steel grades depending on the temperature coil formation. There was obtained the patent of Ukraine for invention no. 91760 «The method for de termining the total and remaining amount of scale on the rolled steel surface».